Uveljavljanje stvarnopravnih zahtevkov v postopkih zaradi insolventnosti - Vrenčur, Renato (Podjetje in delo, 2014)
The application of various instruments of collateral is required in business practice to strengthen the position of creditors in the event of default by debtors, and in particular in bankruptcy or execution. Choosing appropriate collateral is even more important during a recession period, when businesses suffer from a chronic lack of liquidity and insolvency.
Keywords: dolgovi; hipoteka; insolventnost; lastninska pravica; podjetja; prenos; terjatve; zavarovanje